Education, Labor Rights, and Incentives : Contract Teacher Cases in the Indian Courts - Robinson, Nick; Gauri, Varun (2012)
Since the liberalization of India's economy beginning in the early 1990's, the government has increasingly employed contract workers to perform various state functions, including in the education sector. Yet, little research has been done to examine how courts have reacted to this shift in government labor policy. This paper looks at all reported cases involving contract teachers in the Indian Supreme Court and four High Courts over the last thirty years. It finds that although almost never explicitly overturning precedent, the judiciary in India has increasingly become less sympathetic to contract teachers demands, particularly at the Supreme Court level. The paper then argues that the Court could use its power of judicial review to engage the government in a dialogue, not unlike some of its earlier decisions in the 1980s and early 1990s. The Court can help guide the government to create a labor policy that not only achieve better results for students, but better working conditions for teachers. Such a dialogic approach could potentially be adopted to help reframe the government s contract labor policy more generally.